2016
DOI: 10.1002/ana.24672
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea decreases central nervous system–derived proteins in the cerebrospinal fluid

Abstract: We hypothesized that one mechanism underlying the association between obstructive sleep apnea (OSA) and Alzheimer Disease is OSA leading to decreased slow wave activity, increased synaptic activity, decreased glymphatic clearance, and increased amyloid-β. Polysomnography and lumbar puncture were performed in OSA and control groups. Slow wave activity negatively correlated with cerebrospinal fluid amyloid-β-40 among controls and was decreased in the OSA group. Unexpectedly, amyloid-β-40 was decreased in the OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 23 publications
(38 reference statements)
7
118
0
Order By: Relevance
“…Significant inverse associations between SWS and CSF Aβ40 have been found previously in a cohort containing younger middle aged (53.2 ± 5.7) individuals. 25 In any case, the consistent inverse associations between SWS and Aβ42 remain of special interest as this peptide appears to have the greatest propensity to deposit into insoluble plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inverse associations between SWS and CSF Aβ40 have been found previously in a cohort containing younger middle aged (53.2 ± 5.7) individuals. 25 In any case, the consistent inverse associations between SWS and Aβ42 remain of special interest as this peptide appears to have the greatest propensity to deposit into insoluble plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea is one of the most common causes of blood pressure non-dipping. Further, OSA is associated with a reduction of slow wave sleep and lower A␤ 40 in CSF, but in normal control there is an inverse correlation between CSF amyloid level and slow wave activity [36]. Brain interstitial fluid washed through glymphatic system is absorbed into dural lymphatic system and subsequently drained to cervical lymph node [37].…”
Section: Discussionmentioning
confidence: 99%
“…Brain interstitial fluid washed through glymphatic system is absorbed into dural lymphatic system and subsequently drained to cervical lymph node [37]. Repetitive apnea-related intracranial pressure swings are suggested to impair upstream interstitial fluid clearance via glymphatic system [36]. Therefore, reduced amyloid clearance along with increased amyloid production in OSA could accentuate amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, these have never been fully clinically tested in the context of SVD. A recent study demonstrated that obstructive sleep apnea (OSA) causes a reduction in the concentration of brain-derived proteins in CSF after slow wave sleep(123). The authors suggest that OSA causes alterations in CSF-ISF exchange causing these proteins to become trapped when they would normally be cleared out into the CSF.…”
Section: Targeting Glymphatics For Treatment and Prevention Of Svdmentioning
confidence: 99%